Analysis on Temperature Uniformity of Water with Rotation or Stir under Microwave Radiation - Bai1, Yang; Liu1, Xiang-Jun; Li2, Li (Asian Journal of Chemistry, 2014)
Stir, rotation and other methods have been widely used to improve the heating uniformity during microwave heating nowadays. In this paper, the heating uniformity of water with rotation or stir and their combination under microwaves were investigated through multi-physics calculation. It was found that among the three above cases, the temperature uniformity of water under microwave heating with the combination of stir and rotation is the best; the improvement of temperature uniformity of microwave heating water with rotating tray is poor while the speed is increasing and within a certain range, contrarily, increase of the stir speed can significantly improve the temperature uniformity of water and the hotspots cannot be completely dispelled by stir.